TEACHING STUDENTS PROBABILITY THEORY PHARMACEUTICAL FACULTY MEDICAL UNIVERSITY: APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Yurii, Rayisa F. (Educological discourse, 2015)
In the article the features of teaching of probability theory on the pharmaceutical faculty of medical university and question of the use of computer technique in the process of study of disciplines of mathematical cycle by the students of pharmaceutical faculties of medical universities.